2001
DOI: 10.1074/jbc.m011175200
|View full text |Cite
|
Sign up to set email alerts
|

The Recruitment of SOX/OCT Complexes and the Differential Activity of HOXA1 and HOXB1 Modulate the Hoxb1Auto-regulatory Enhancer Function

Abstract: Regionally restricted expression patterns of Hox genes in developing embryos rely on auto-, cross-, and pararegulatory transcriptional elements. One example is the Hoxb1 auto-regulatory element (b1-ARE), which drives expression of Hoxb1 in the fourth rhombomere of the hindbrain. We previously showed that HOXB1 and PBX1 activate transcription from the b1-ARE by binding to sequences required for the expression of a reporter gene in rhombomere 4 in vivo. We now report that in embryonal carcinoma cells, which reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 57 publications
(94 reference statements)
3
70
0
Order By: Relevance
“…These results demonstrated that Hoxa1 is required for the transcriptional activation of Hoxb1 by RA in these ES cell lines. Our results using these ES cells are in agreement with previous observations reported in the literature for other model systems (23,24,26,32,43).…”
Section: Induction Of Hoxa Cluster Gene Expression By Ra In the Absensupporting
confidence: 83%
See 2 more Smart Citations
“…These results demonstrated that Hoxa1 is required for the transcriptional activation of Hoxb1 by RA in these ES cell lines. Our results using these ES cells are in agreement with previous observations reported in the literature for other model systems (23,24,26,32,43).…”
Section: Induction Of Hoxa Cluster Gene Expression By Ra In the Absensupporting
confidence: 83%
“…and Hoxa1 Ϫ/Ϫ ES Cells-It has been demonstrated that Hoxa1 is required for the correct expression levels of Hoxb1 both in vitro and in vivo (23,26,32,43). To determine whether this is the case in our model system, we examined the expression of Hoxb1 in the three ES cell lines with or without RA treatment ( Fig.…”
Section: Induction Of Hoxa Cluster Gene Expression By Ra In the Absenmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding sites for Oct-1 and Pbx1/Prep1 in the Ϫ1603 enhancer element as well as in the Ϫ100 promoter element actually overlap each other, whereas the Ϫ1749 enhancer TALE site and the Ϫ75 promoter TALE site are separated from Oct-1-binding sites by 25 and 21 bp, respectively. The observation of clustered Oct-1-and Pbx1/ Prep1-binding sites in promoter regions has also been reported in the context of the urokinase enhancer (42), the Hoxb1 auto-regulatory enhancer (43), and the UDP-glucuronosyltransferase 2B15A promoter (49). Similarly, we observed four of these clustered binding elements dispersed throughout the GnRH enhancer and promoter regions.…”
Section: Discussionsupporting
confidence: 55%
“…Transcription factors involved in Hox gene regulation include HOX proteins themselves, acting with PBX, 3 MEIS, and PREP cofactors (9, 10), Kreisler (11), KROX20 (12), and Sox-Oct family members (13). One of the most important factors regulating Hox gene expression is retinoic acid (RA) (14).…”
mentioning
confidence: 99%